Dimensions of emancipatory education from freire and vigotsky perspective: human development - Schmidt Brasil, Magda; Clotildes Felix Gabry, Maria; Martins, Olga (Seven Editora, 2023)
This research aims to point out education as a fundamental part of integral development, with the commitment to prepare students for a more prosperous society. As well-planned, education can contribute to the formation of more skilled individuals in a peaceful and sustainable society, forming people in all dimensions, especially throughout life, having as a proposal: construction of collective knowledge for protagonism and social transformation. DOI: https://doi.org/10.56238/tfisdwv1-038